Penguatan Hasil Belajar Peserta Didik Terhadap Assesmen Dengan Memanfaatkan Paradigma Baru - Anjarwati, Ani; Az-Zahra, Putri Fatimattus; Putri, Dita Refani; Kunanti, Rr Ghina Ayu Putri Tya; Diana, Dewi Rafika Nur (CV. ITTC INDONESIA, 2022)
In the 21st century learning period requires educators to be more skilled in processing learning media as creatively as possible by utilizing current technological developments. Utilization of this technology can be used as a solution to improve student learning outcomes in understanding HOTS assessment. This research was conducted at Kedungdalem 2 Public Elementary School Class 5 by focusing on the material